(Dis)entangling Barad: Materialisms and ethics. (December 2017) - Hollin, Gregory; Forsyth, Isla; Giraud, Eva; Potts, Tracey
In the wake of the widespread uptake of and debate surrounding the work of Karen Barad, this article revisits her core conceptual contributions. We offer descriptions, elaborations, problematizations and provocations for those intrigued by or invested in this body of work. We examine Barad's use of quantum physics, which underpins her conception of the material world. We discuss the political strengths of this position but also note tensions associated with applying quantum physics to phenomena at macro-scales. We identify both frictions and unacknowledged affinities with science and technology studies in Barad's critique of reflexivity and her concept of diffraction. We flesh out Barad's overarching position of 'agential realism', which contains a revised understanding of scientific apparatuses. Building upon these discussions, we argue that inherent in agential realism is both an ethics of inclusion and an ethics of exclusion. Existing research has, however, frequently emphasized entanglement and inclusion to the detriment of foreclosure and exclusion. Nonetheless, we contend that it is in the potential for an ethics of exclusion that Barad's work could be of greatest utility within science and technology studies and beyond.